ΒAPP Processing Drives Gradual Tau Pathology in an Age-Dependent Amyloid Rat Model of Alzheimer's Disease. (18th October 2017) - Audrain, Mickael; Souchet, Benoit; Alves, Sandro; Fol, Romain; Viode, Arthur; Haddjeri, Alexis; Tada, Satoru; Orefice, Nicola S; Joséphine, Charlène; Bemelmans, Alexis-Pierre; Delzescaux, Thierry; Déglon, Nicole; et al.
Abstract: The treatment of Alzheimer's disease (AD) remains challenging and requires a better in depth understanding of AD progression. Particularly, the link between amyloid protein precursor (APP) processing and Tau pathology development remains poorly understood. Growing evidences suggest that APP processing and amyloid-β (Aβ) release are upstream of Tau pathology but the lack of animal models mimicking the slow progression of human AD raised questions around this mechanism. Here, we described that an AD-like βAPP processing in adults wild-type rats, yielding to human APP, βCTF and Aβ levels similar to those observed in AD patients, is sufficient to trigger gradual Tauopathy. The Tau hyperphosphorylation begins several months before the formation of both amyloid plaques and tangle-like aggregates in aged rats and without associated inflammation. Based on a longitudinal characterization over 30 months, we showed that extrasynaptic and emotional impairments appear before long-term potentiation deficits and memory decline and so before Aβ and Tau aggregations. These compelling data allowed us to (1) experimentally confirm the causal relationship between βAPP processing and Tau pathology in vivo and without Tau transgene overexpression, (2) support the amyloidogenic cascade and (3) propose a 4-step hypothesis of prodromal AD progression.